Konsep Learning Culture: Telaah Pemikiran al-Zarnujy dalam Kitab Ta‘lîm al-Muta‘allim - Isti’anah Abubakar (Universitas Darussalam Gontor, 2018)
The world has made learning as an organizational advantage. A superior organization is capable to manage the learning potency of its members into a culture. Discussion of learning culture as the basis of learning organization so far is still dominated by Western thought, especially Peter Senge and Marquadt. Peter Senge has The Fift Discipline as an individual and organizational learning skill. These fve disciplines were corroborated by Marquadt by adding dialogue as his learning skill. This study tries to explore the classic book that can be used as a comparison of learning culture, considering learning to be the spirit of Islam. Al-Zarnujy became an option considering his integrity and his book was phenomenal and monumental. The concept of learning culture is characterized by three things, they are values, learning process, and creating conditions described in full and detail. In values, al-Zarnujy gives three things to straighten the intention as a foothold, they are to againsts ignorance, to do syiar, and to be grateful for the pleasure of sense and healthy body. As for the learning process is also described very detail about how to learn, about ethics, and some things to avoid. Creating conditions is emphasized in the foresight and intelligence to choose friends, who are pious and understand the current condition. Through this article, the author asserts that the contents of al-Zarnujy’s book is still relevant today. The author begins by describing the socio-historical background of al-Zarnujy and his book, then the concept of learning culture in it.